Perbedaan Pengaruh Aerobic Low Impact Exercise dan Gaze Stability Exercise terhadap Keseimbangan Dinamis - Apriyani, Ishela; Norlinta, Siti Nadhir Ollin; Jannah, Suci Muqodimmatul (Jurnal Kesmas Asclepius, 2025)
This study aims to determine the differences in the effects of the two exercises on the dynamic balance of the elderly. The research method uses a 2-group quasi-experimental design with a "pre-test - post-test" design. A total of 40 elderly people at BPSTW Budi Luhur, Bantul Regency were divided into two groups, namely Aerobic Low Impact Exercise and Gaze Stability Exercise. The results of this study from the hypothesis test 1 using Wilcoxon showed a score of p = 0.000 (p <0.05), which indicates that there is a significant effect of Aerobic Low Impact Exercise. The results of the hypothesis test 2 with a paired sample t-test showed p = 0.000 (p <0.05), there is an effect of gaze stability on dynamic balance in the elderly. The results of the Independent sample t-test showed a score of p = 0.000 (p <0.05) indicating that there is a significant difference between Aerobic Exercise and Gaze Stability Exercise on improving dynamic balance in the elderly at BPSTW Budi Luhur. The conclusion shows that Aerobic Low Impact Exercise and Gaze Stability Exercise both have an effect on improving dynamic balance in the elderly. However, Gaze Stability Exercise has a significant effect compared to Aerobic Low Impact Exercise. Keywords: Aerobic Low Impact Exercise, Dynamic Balance, Gaze Stability Exercise, Elderly.